Antiproliferative and apoptotic effects of onobrychis albiflora extract on HCT-116 cells - Bülbül, Muhammet Volkan; Özbek, Hanefi; Bahadır Acıkara, Özlem; Özbilgin, Serkan; Ergene Öz, Burçin; Kurtul, Ekin; Keskin, İlknur (Ondokuz Mayıs University, 2018)
In this study, the cytotoxic effects of the extracts of methanol: water (80:20) prepared from the above-ground parts of the varieties of Onobrychis albiflora Hub.-Mor., Onobrychis argyrea Boiss. subsp. argyrea, Onobrychis galegifolia Boiss. and Onobrychis tournefortii (Willd.) Desv. species to HCT-116 cells were investigated. With cytotoxicity analysis that with these species inhibitor concentrations (IC50) which resulted in a 50% reduction in the proliferation of HCT-116 cells were identified. In continuation of the study; the antiproliferative and apoptotic effects of Onobrychis albiflora extract on HCT-116 cells were evaluated by Caspase 3, Annexin V / PI Apoptosis / Necrosis analysis, Apopxin Green and 7-AAD Apoptosis / Necrosis analysis. The antiproliferative, apoptotic and necrotic effects of Onobrychis albiflora extract on HCT-116 cells also were determined.
Keywords: Apoptosis; Flow Cytometry; HCT-116; HEK-293; Necrosis